2012
DOI: 10.1007/s12282-011-0327-9
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in patients with breast cancer using superparamagnetic iron oxide and a magnetometer

Abstract: This is the first study to use a magnetic tracer to identify sentinel lymph nodes in patients with breast cancer. This new technique may alter the role of radioisotopes with further refinement and experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 18 publications
3
60
0
Order By: Relevance
“…However, the false negative rate has been unacceptably high in studies of magnetic SLNB. Shiozawa et al [16] (would be good here to list how many patients, and maybe give this trial a name to -to be consistent with he other two) reported a false negative rate of 17 per cent using the magnetic technique and even the SentiMAG Multicentre Trial, [17] which was found to be non-inferior to the dual technique for SLN identification demonstrated a false negative rate of 8 per cent and 4 per cent for the magnetic and dual techniques respectively. The Central-European SentiMag Study [18] identified a lower false negative rate for the magnetic technique of 3 per cent versus 9 per cent for the standard radioisotope technique, inconsistent with the previous studies.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…However, the false negative rate has been unacceptably high in studies of magnetic SLNB. Shiozawa et al [16] (would be good here to list how many patients, and maybe give this trial a name to -to be consistent with he other two) reported a false negative rate of 17 per cent using the magnetic technique and even the SentiMAG Multicentre Trial, [17] which was found to be non-inferior to the dual technique for SLN identification demonstrated a false negative rate of 8 per cent and 4 per cent for the magnetic and dual techniques respectively. The Central-European SentiMag Study [18] identified a lower false negative rate for the magnetic technique of 3 per cent versus 9 per cent for the standard radioisotope technique, inconsistent with the previous studies.…”
Section: Introductionsupporting
confidence: 52%
“…This means that the control of the performance of SLNB is directly within the hands of the operating surgeon who administers the magnetic tracer. All 3 published clinical studies [16][17][18] for the use of the magnetic technique injected the magnetic tracers after induction of general anaesthetic, periareolarly into the breast. Although the optimal timing of the magnetic tracer is not yet known, our results suggest that a pre-operative injection (4 hours or more prior to surgery) is likely to significantly improve the percutaneous magnetometer count and by doing so, improve the identification rate.…”
Section: ]mentioning
confidence: 99%
See 3 more Smart Citations